PREVALENCE OF COMPLICATIONS IN TYPE 2 DIABETES MELLITUS IN A TERITARY CARE HOSPITAL - A PROSPECTIVE STUDY - SHREEN, SARA; UDDIN, MOHAMMED BALEEQH; ALI, MIR SALMAN; SULTANA, ZOHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
drgdfgh